An Ethnobotanical Study to Species Used as Upakara Materials in Ngerebong Ceremony in Kesiman Village, Denpasar City - Handayani, Ni Luh Nyoman Vivi Tri; Juliasih, Ni Ketut Ayu; Arsana, I Nyoman; Suardana, A.A. Komang (ECOTAS, 2023)
The ngerebong ceremony held in Pakraman Kesiman Village, Denpasar City, has been carried out for generations by the local community. Nevertheless, studies have not determined what living things were used in the ritual. This study aims to identify species used as upakara ingredients in the Ngerebong ritual with an ethnobotanical study approach. The mixed-methods research design was used for two months. Data analysis is carried out descriptively. The findings showed that 39 species of plants, consisting of 25 families, were used as material for making banten. The parts used consist of stems, leaves, flowers, fruits, roots, and tubers. The components used include water, wine (berem), white thread, salt, anchovies, whiting, duck eggs, chicken eggs, pennies, incense, eel, babi guling, rupiah bills, chicken satay, and gauze. The complexity of materials used in the ngerebong ceremony makes it necessary to conserve and preserve biological resources in order to maintain their existence.